A method for preparing pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures

By growing indium arsenide molecules on the inner wall of graphene nanotubes and controlling the growth time to prepare indium arsenide nanowires or two-dimensional layered structures of pure wurtzite crystal phase, the problem of difficulty in controlling the crystal structure of indium arsenide nanowires in the prior art is solved, and the purity and device performance of the nanowires are improved.

CN116463611BActive Publication Date: 2025-04-29NANTONG UNIV
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202310476095.3
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-04-28
Publication Date
2025-04-29
Estimated Expiration
2043-04-28

AI Technical Summary

Technical Problem

The prior art is difficult to effectively control the crystal structure of indium arsenide nanowires, resulting in scattering problems of carriers and phonons, affecting the normal operation of the device.

Method used

Graphene nanotubes are prepared using diamond nanoparticles as substrates. By growing indium arsenide molecules on the inner wall of graphene nanotubes, the growth time is controlled to prepare indium arsenide nanowires or two-dimensional layered structures of pure wurtzite crystal phase.

Benefits of technology

Accurate control of the crystal structure of indium arsenide nanowires is achieved, the purity and stability of the nanowires are improved, and the electrical and optical properties of the devices are optimized.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116463611B_ABST
    Figure CN116463611B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing an indium arsenide nanowire or a two-dimensional layered structure of a pure wurtzite crystal phase, wherein an indium arsenide substrate layer is prepared; a graphene nanotube of a desired size is prepared using diamond nanoparticles, the prepared graphene nanotube is longitudinally placed on the substrate layer, and silver is deposited on the substrate layer as a catalyst; the graphene nanotube and the substrate layer are quickly transferred to a loading chamber of an MBE reactor, and catalytic preparation of the indium arsenide nanowire begins; the indium arsenide molecules grow radially along the inner wall of the graphene nanotube, and the growth time of the indium arsenide molecules is controlled to obtain a graphene nanotube containing an indium arsenide nanowire or a two-dimensional layered structure; the treated graphene nanotube is subjected to heat treatment to obtain a graphene nanotube opened along the longitudinal axis, and the indium arsenide nanowire or the two-dimensional layered structure of a pure wurtzite crystal phase is separated and obtained. The preparation method of the invention can efficiently prepare indium arsenide nanowires or two-dimensional layered structures with better performance, and reduce production costs.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of nanomaterials, and in particular to a method for preparing a pure wurtzite crystal phase indium arsenide nanowire or a two-dimensional layered structure. Background Art

[0002] Nanomaterials are a hot topic in the world today. Due to the special structure, they are widely used in nano-optoelectronic devices. III-V semiconductor materials have the advantages of direct band gap, high electron mobility, small effective mass, and excellent electrical and optical properties, making nanowires made of III-V materials an ideal material for the preparation of electronic and optoelectronic devices. Indium arsenide (InAs) is an important narrow bandgap semiconductor material with high electron mobility and low effective mass. Nanowires made of indium arsenide have the characteristics of both InAs materials and low-dimensional nanomaterials. Therefore, indium arsenide nanowires are ideal materials for the preparation of single-electron transistors, resonant tunneling diodes and ballistic transport transistors, and have great application value and scientific significance.

[0003] As the research on nanowire devices becomes more and more extensive, the requirements for the quality of nanowires themselves are getting higher and higher. Precise size control, lattice orientation, phase purity and uniform composition are all key factors in the preparation of nanowires. The morphology and size of nanowires are very important. First, within the nanometer scale, a small change in size may have a huge impact on the overall performance of the device. Secondly, the performance of many devices has an important dependence on the diameter of the nanowire. Finally, the crystal structure of the semiconductor directly determines the band structure. Different crystal structures of wurtzite structure (WZ) or zinc blende structure (ZB) directly affect the characteristics of carriers in the device. Therefore, it is very important to control the length, diameter and crystal structure of nanowires. Devices prepared with small-sized and wurtzite-structured nanowires have excellent performance.

[0004] At present, the preparation methods of nanowires can be divided into two categories: top-down and bottom-up. The top-down growth mechanism is a method of using flat-plate imprinting technology to carve three-dimensional indium arsenide materials into one-dimensional nanowires. However, as the size of the device continues to decrease, it becomes increasingly difficult to control the size and growth direction of the nanowires. The top-down preparation method is difficult to meet the preparation of small-sized nanostructures due to the limited resolution of its photolithography and etching technologies; at the same time, the preparation of nanowires by the top-down growth mechanism has the problem of wasting materials. The bottom-up growth mechanism is to self-assemble indium atoms and arsenic atoms at the nanoscale through weak interactions to form nanowires. This synthesis mechanism can synthesize more delicate structures, and can also control the length, diameter and crystal structure of the grown indium arsenide nanowires according to needs. Therefore, the bottom-up preparation method can design and construct more complex nanostructure devices. The introduction of this preparation method has promoted the development of nanostructure devices.

[0005] In order to fully utilize the excellent physical properties of InAs nanowires, controlling the crystal structure in practical device applications is a prerequisite, because the crystal structure largely determines the electrical and optical properties. Figure 2 As shown, when InAs nanowires are prepared under traditional conditions, the crystal structure of InAs nanowires gradually evolves from WZ and WZ / ZB with a small amount of (stacking faults (SF) + twin planes (TP)) to a (WZ+ZB) mixture with a high density (SF+TP) in the growth direction. The twins, stacking disorder and polymorphic inhomogeneous phases that appear in this case will cause scattering problems of carriers and phonons, and even seriously affect the normal operation of the device. The two-dimensional layered structure of InAs can also reduce the effective carrier capture state. Therefore, an important criterion for ensuring the excellent performance of nanostructured devices is that the InAs nanowires are pure wurtzite crystal phases and have a two-dimensional layered structure. Summary of the invention

[0006] Purpose of the invention: The purpose of the present invention is to provide a method for preparing indium arsenide nanowires or two-dimensional layered structures in a pure wurtzite crystal phase, so as to solve the problem of preparing indium arsenide nanowires or two-dimensional layered structures.

[0007] Technical solution: The method for preparing a pure wurtzite crystal phase indium arsenide nanowire or a two-dimensional layered structure of the present invention comprises the following steps:

[0008] Step S1: preparing a substrate layer;

[0009] Step S2: using diamond nanoparticles to prepare graphene nanotubes of a desired size, and placing the prepared graphene nanotubes longitudinally on the substrate layer prepared in step S1;

[0010] Step S3: depositing Ag droplets with a thickness of 0.5-1.5 nm on the substrate layer below the graphene nanotubes as a catalyst;

[0011] Step S4: quickly transferring the graphene nanotubes and the substrate layer into the loading chamber of the MBE reactor, opening the reactor, and starting catalytic preparation of indium arsenide nanowires;

[0012] Step S5: InAs molecules grow radially along the inner wall of the graphene nanotube, controlling the growth time of the InAs molecules to obtain InAs nanowires or two-dimensional layered structures of pure wurtzite crystal phase, and then closing the MBE reactor;

[0013] Step S6: heat-treating the graphene nanotubes processed in step S5 to obtain graphene nanotubes opened along the longitudinal axis, and separating to obtain pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures.

[0014] Preferably, the specific preparation steps of step S1 are as follows:

[0015] Step S 11 : Preparing an indium arsenide layer of a required size as a substrate layer;

[0016] Step S 12 : The substrate layer is chemically cleaned using a standard wet etching method using acetone, methanol, isopropanol and deionized water;

[0017] Step S 13 : Use hydrofluoric acid solution to deoxidize the substrate layer; wherein the concentration of the hydrofluoric acid solution is: hydrofluoric acid: deionized water = 1:20.

[0018] Preferably, the specific preparation steps of step S2 are as follows:

[0019] Step S 21 : Disperse 0.02-0.04 g of 5-10 nm diamond nanoparticles in 150-250 ml of anhydrous ethanol to prepare a diamond suspension;

[0020] Step S 22 : Place a SiO2 substrate with a thickness of 45-55 nm in a diamond suspension and soak for 10-30 min;

[0021] Step S 23 : After the substrate plate is dried, the substrate plate is placed in a quartz tube of a horizontal resistance furnace and heated to 800-1000° C. in an argon atmosphere to crack the diamond nanoparticles;

[0022] Step S 24: 900-1100 ml / min of methane and 90-110 ml / min of hydrogen are introduced to generate carbon atoms or carbon clusters; after reacting for 45-70 minutes, the methane and hydrogen are turned off, and the quartz tube of the electric furnace is cooled to room temperature under an argon atmosphere, and the carbon atoms or carbon clusters are aggregated on the SiO2 substrate to form graphene nanotubes.

[0023] Preferably, the specific steps of step S6 are as follows:

[0024] Step S 61 : placing the graphene nanotubes treated in step S5 into an induction furnace and performing heat treatment at a temperature of 600-800° C.;

[0025] Step S 62 : After the heat treatment is continued for 50-70 min, 90-110 sccm of nitrogen is introduced into the induction furnace to rapidly cool the graphene nanotubes;

[0026] Step S 63 : Use a transmission electron microscope to observe whether the graphene nanotubes after heat treatment are successfully opened. If not, repeat step S 61 , S 62 , obtaining a graphene nanotube opened along the axial direction.

[0027] Preferably, the step S7 of removing the catalyst silver is included, and the specific steps are as follows:

[0028] Step S 71 : Clean the indium arsenide nanowires or two-dimensional layered structures prepared in step S6 with 150-250 ml of anhydrous ethanol, and repeat the cleaning twice to remove impurities and contaminants remaining on the surface of the indium arsenide nanowires or two-dimensional layered structures;

[0029] Step S 72 : Transfer the indium arsenide nanowires or two-dimensional layered structures into a beaker, add a mixed solution of 3-5 mol nitric acid and 1-2 mol hydrofluoric acid, and soak for 10-30 min, so that the Ag catalyst is chemically corroded and dissolved;

[0030] Step S 73 : Taking out the indium arsenide nanowires or two-dimensional layered structures from the mixed solution, and repeatedly washing them with deionized water to remove the residues of the chemical etching solution;

[0031] Step S 74 : 90-110 sccm of nitrogen is introduced into the indium arsenide nanowire or two-dimensional layered structure for 5-10 minutes to obtain an indium arsenide nanowire or two-dimensional layered structure without Ag catalyst.

[0032] Preferably, the substrate layer prepared in step S1 has a thickness of 4-6 μm, and a length and width of 50-70 μm.

[0033] Preferably, the graphene nanotubes prepared in step S2 have a diameter of 25-35 μm and a length of 15-25 μm.

[0034] Preferably, in step S5, the growth time of the indium arsenide molecules is controlled to be 10-20 min, so that indium arsenide nanowires in a pure wurtzite crystal phase can be obtained.

[0035] Preferably, in step S5, the growth time of the indium arsenide molecules is controlled to be 100-140 min, so that a two-dimensional layered structure of indium arsenide in a pure wurtzite crystal phase can be obtained.

[0036] Preferably, the length of the indium arsenide nanowire or the diameter of the two-dimensional layered structure is not greater than the inner diameter of the graphene nanotube.

[0037] Beneficial effects: Compared with the prior art, the present invention has the following outstanding advantages:

[0038] 1. The indium arsenide nanowires prepared by the present invention are pure wurtzite crystal phase indium arsenide nanowires. The length of the nanowires is controlled by the radius of the graphene nanotubes, and the length of the graphene nanotubes can reach the micron level. Devices made of high-precision pure wurtzite crystal phase indium arsenide nanowires have better performance and are widely used.

[0039] 2. The two-dimensional layered structure of indium arsenide of the present invention is formed by the self-aggregation effect of indium arsenide nanowires in the pure wurtzite crystal phase continuing to grow and being connected by van der Waals forces between the nanowires, without adding other process steps, thereby reducing production costs;

[0040] 3. The prepared two-dimensional layered structure of indium arsenide is based on the van der Waals force between nanowires, and the two-dimensional layered structure is easily peeled off from the indium arsenide nanowires, thereby obtaining a two-dimensional layered structure of indium arsenide;

[0041] 4. Using graphene nanotubes as the substrate structure for the growth of indium arsenide molecules, compared with traditional graphene layers, the indium arsenide nanowires grown on the inner wall of graphene nanotubes have higher yields, simpler preparation processes, lower costs, and can generate two-dimensional layered structures;

[0042] 5. Using an indium arsenide layer as the substrate layer, when using an Ag catalyst, indium arsenide nanowires will not grow on the surface of the indium arsenide substrate layer, and the nanowires will only grow on the inner wall of the graphene nanotubes, and the obtained indium arsenide nanowires or two-dimensional layered structures will have better quality;

[0043] 6. Indium arsenide molecules grow circumferentially within graphene nanotubes, and the number of indium arsenide nanowires grown increases significantly, thereby improving the preparation efficiency of indium arsenide nanowires or two-dimensional layered structures and reducing device production costs. BRIEF DESCRIPTION OF THE DRAWINGS

[0044] Figure 1 It is a structural schematic diagram of the method for preparing pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures of the present invention;

[0045] Figure 2 The image of the crystal phase in the growth direction of InAs nanowires is the transformation from WZ and WZ / ZB to ZB+WZ;

[0046] Figure 3 Top view of indium arsenide nanowires prepared for pure wurtzite crystal phase

[0047] Figure 4 A top view of the two-dimensional layered structure of indium arsenide is prepared;

[0048] Figure 5 A flow chart of preparing pure wurtzite crystal phase indium arsenide nanowires according to the present invention;

[0049] Figure 6 The present invention is a flow chart for preparing a two-dimensional layered structure of indium arsenide in a pure wurtzite crystal phase.

[0050] Reference numerals:

[0051] 1. Substrate layer; 2. Graphene nanotubes; 3. Indium arsenide nanowires; 4. Two-dimensional layered structure. DETAILED DESCRIPTION

[0052] To make the purpose, technical solution and advantages of the embodiments of the present invention clearer, the following will be combined with the appended drawings of the embodiments of the present invention. Figure 1-6 , the technical scheme of the embodiment of the present invention is clearly and completely described. Obviously, the described embodiment is a part of the embodiment of the present invention, not all of the embodiments. Based on the described embodiment of the present invention, all other embodiments obtained by ordinary technicians in this field belong to the scope of protection of the present invention.

[0053] like Figure 1 As shown, a method for preparing an indium arsenide nanowire or a two-dimensional layered structure of a pure wurtzite crystal phase of the present invention, the structures required for the preparation method are, from bottom to top, an indium arsenide substrate layer 1 and a graphene nanotube 2, the indium arsenide substrate layer 1 being placed at the bottom as a substrate during preparation, and the graphene nanotube 2 being arranged on the substrate layer 1 along the longitudinal direction; the graphene nanotube 2 is prepared from diamond nanoparticles; the indium arsenide nanowire 3 and the two-dimensional layered structure 4 are grown radially on the inner wall of the graphene nanotube 2.

[0054] Embodiment 1:

[0055] like Figure 3 and 5 As shown, a method for preparing pure wurtzite crystal phase indium arsenide nanowires of the present invention comprises the following steps:

[0056] Step S1: Preparing the substrate layer 1 comprises the following steps:

[0057] Step S 11 : Prepare an indium arsenide layer with a thickness of 5 μm and a length and width of 60 μm as the substrate layer 1;

[0058] Step S 12 : The substrate layer 1 is chemically cleaned by a standard wet etching method using acetone, methanol, isopropanol and deionized water;

[0059] Step S 13 : Deoxidation treatment is performed on the substrate layer 1 using a hydrofluoric acid solution; wherein the concentration of the hydrofluoric acid solution is: hydrofluoric acid: deionized water = 1:20;

[0060] Step S2: Use diamond nanoparticles to prepare graphene nanotubes 2 with a diameter of 30 μm and a length of 20 μm, and the length of the indium arsenide nanowires 3 is not greater than the inner diameter of the graphene nanotubes 2; place the prepared graphene nanotubes 2 longitudinally on the substrate layer 1; the size of the graphene nanotubes can be controlled by controlling the immersion time of the SiO2 substrate in the diamond suspension and the concentration of diamond nanoparticles in the diamond suspension to control the number and distribution of diamond nanoparticles adsorbed on the surface of the SiO2 substrate; then, the size of the graphene nanotubes is controlled by adjusting parameters such as the heating temperature, the flow rate of methane and hydrogen, and the reaction time; generally speaking, increasing the heating temperature and the methane flow rate can promote the growth rate and diameter of the graphene nanotubes, while also reducing their length. The specific preparation steps of the graphene nanotubes 2 are as follows:

[0061] Step S 21 : Disperse 0.02 g of 8 nm diamond nanoparticles in 150 ml of anhydrous ethanol to prepare a diamond suspension;

[0062] Step S 22 : Place a 50 nm thick SiO2 substrate in a diamond suspension and soak for 30 min;

[0063] Step S 23 : After the substrate plate is dried, the substrate plate is placed in a quartz tube of a horizontal resistance furnace and heated to 800° C. in an argon atmosphere to crack the diamond nanoparticles;

[0064] Step S 24: 900 ml / min of methane and 90 ml / min of hydrogen are introduced to generate carbon atoms or carbon clusters; after reacting for 70 minutes, the methane and hydrogen are turned off, and the quartz tube of the electric furnace is cooled to room temperature under an argon atmosphere, and the carbon atoms or carbon clusters are aggregated on the SiO2 substrate to form graphene nanotubes;

[0065] Step S3: depositing a 1.0 nm thick Ag droplet as a catalyst on the substrate layer 1 below the graphene nanotube 2; Ag as a catalyst can inhibit the growth of indium arsenide molecules along the surface of the substrate layer 1, and the indium arsenide molecules only grow radially along the inner wall of the graphene nanotube, so that the obtained indium arsenide nanowire 3 has better quality;

[0066] Step S4: quickly transferring the graphene nanotubes and the substrate layer into the loading chamber of the MBE reactor, opening the reactor, and starting catalytic preparation of the indium arsenide nanowires 3;

[0067] Step S5: InAs molecules grow radially along the inner wall of the graphene nanotube 2, and the growth time of the InAs molecules is controlled to be 10 min, so that the InAs nanowire 3 of pure wurtzite crystal phase can be obtained, and then the MBE reactor is closed;

[0068] Step S6: heat-treating the treated graphene nanotubes to obtain graphene nanotubes opened along the longitudinal axis, and separating to obtain pure wurtzite crystal phase indium arsenide nanowires; the specific steps of radially opening the graphene nanotubes are as follows:

[0069] Step S 61 : Put the graphene nanotubes into an induction furnace and perform heat treatment at a temperature of 600 °C;

[0070] Step S 62 : After the heat treatment was continued for 70 min, 90 sccm of nitrogen was introduced into the induction furnace to rapidly cool the graphene nanotubes;

[0071] Step S 63 : Using a transmission electron microscope to observe whether the graphene nanotubes after heat treatment are successfully opened, if not successfully opened, repeating the heat treatment to obtain graphene nanotubes opened along the axial direction;

[0072] Step S7: The specific steps of removing the catalyst silver are as follows:

[0073] Step S 71 : Clean the indium arsenide nanowires prepared in step S6 with 200 ml of anhydrous ethanol, and repeat the cleaning twice to remove impurities and contaminants remaining on the surface of the indium arsenide nanowires;

[0074] Step S 72: Transfer the indium arsenide nanowires to a beaker, add a mixed solution of 3 mol nitric acid and 1 mol hydrofluoric acid, and soak for 30 min to chemically corrode and dissolve the Ag catalyst;

[0075] Step S 73 : The indium arsenide nanowires are taken out from the mixed solution and repeatedly cleaned with deionized water to remove the residues of the chemical corrosion solution;

[0076] Step S 74 : After 90 sccm of nitrogen was introduced into the InAs nanowires for 10 min, InAs nanowires without Ag catalyst were obtained.

[0077] Removing the catalyst Ag can avoid affecting the surface and interface properties of InAs nanowires, thereby maintaining the electrical, optical and chemical properties of InAs nanowires unchanged, improving the purity and stability of InAs nanowires, and thus optimizing their performance and applications.

[0078] Embodiment 2:

[0079] like Figure 3 and 5 As shown, a method for preparing pure wurtzite crystal phase indium arsenide nanowires of the present invention comprises the following steps:

[0080] Step S1: Preparing the substrate layer 1 comprises the following steps:

[0081] Step S 11 : Prepare an indium arsenide layer with a thickness of 5 μm and a length and width of 60 μm as the substrate layer 1;

[0082] Step S 12 : The substrate layer 1 is chemically cleaned by a standard wet etching method using acetone, methanol, isopropanol and deionized water;

[0083] Step S 13 : Deoxidation treatment is performed on the substrate layer 1 using a hydrofluoric acid solution; wherein the concentration of the hydrofluoric acid solution is: hydrofluoric acid: deionized water = 1:20;

[0084] Step S2: Use diamond nanoparticles to prepare graphene nanotubes 2 with a diameter of 30 μm and a length of 20 μm, and the length of the indium arsenide nanowires 3 is not greater than the inner diameter of the graphene nanotubes 2; place the prepared graphene nanotubes 2 longitudinally on the substrate layer 1; the size of the graphene nanotubes can be controlled by controlling the immersion time of the SiO2 substrate in the diamond suspension and the concentration of diamond nanoparticles in the diamond suspension to control the number and distribution of diamond nanoparticles adsorbed on the surface of the SiO2 substrate; then, the size of the graphene nanotubes is controlled by adjusting parameters such as the heating temperature, the flow rate of methane and hydrogen, and the reaction time; generally speaking, increasing the heating temperature and the methane flow rate can promote the growth rate and diameter of the graphene nanotubes, while also reducing their length. The specific preparation steps of the graphene nanotubes 2 are as follows:

[0085] Step S 21 : Disperse 0.04 g of 8 nm diamond nanoparticles in 250 ml of anhydrous ethanol to prepare a diamond suspension;

[0086] Step S 22 : Place a 50 nm thick SiO2 substrate in the diamond suspension and soak for 10 min;

[0087] Step S 23 : After the substrate plate is dried, the substrate plate is placed in a quartz tube of a horizontal resistance furnace and heated to 1000° C. in an argon atmosphere to crack the diamond nanoparticles;

[0088] Step S 24 : 1100 ml / min of methane and 110 ml / min of hydrogen are introduced to generate carbon atoms or carbon clusters; after reacting for 45 minutes, the methane and hydrogen are turned off, and the quartz tube of the electric furnace is cooled to room temperature under an argon atmosphere, and the carbon atoms or carbon clusters are aggregated on the SiO2 substrate to form graphene nanotubes;

[0089] Step S3: depositing a 1.0 nm thick Ag droplet as a catalyst on the substrate layer 1 below the graphene nanotube 2; Ag as a catalyst can inhibit the growth of indium arsenide molecules along the surface of the substrate layer 1, and the indium arsenide molecules only grow radially along the inner wall of the graphene nanotube, so that the obtained indium arsenide nanowire 3 has better quality;

[0090] Step S4: quickly transferring the graphene nanotubes and the substrate layer into the loading chamber of the MBE reactor, opening the reactor, and starting catalytic preparation of the indium arsenide nanowires 3;

[0091] Step S5: InAs molecules grow radially along the inner wall of the graphene nanotube 2, and the growth time of the InAs molecules is controlled to be 20 min, so that the InAs nanowire 3 of pure wurtzite crystal phase can be obtained, and then the MBE reactor is closed;

[0092] Step S6: heat-treating the treated graphene nanotubes to obtain graphene nanotubes opened along the longitudinal axis, and separating to obtain pure wurtzite crystal phase indium arsenide nanowires; the specific steps of radially opening the graphene nanotubes are as follows:

[0093] Step S 61 : Put the graphene nanotubes into an induction furnace and perform heat treatment at a temperature of 800 °C;

[0094] Step S 62 : After the heat treatment was continued for 50 min, 110 sccm of nitrogen was introduced into the induction furnace to rapidly cool the graphene nanotubes;

[0095] Step S 63 : Using a transmission electron microscope to observe whether the graphene nanotubes after heat treatment are successfully opened, if not successfully opened, repeating the heat treatment to obtain graphene nanotubes opened along the axial direction;

[0096] Step S7: The specific steps of removing the catalyst silver are as follows:

[0097] Step S 71 : Clean the indium arsenide nanowires prepared in step S6 with 200 ml of anhydrous ethanol, and repeat the cleaning twice to remove impurities and contaminants remaining on the surface of the indium arsenide nanowires;

[0098] Step S 72 : Transfer the indium arsenide nanowires to a beaker, add a mixed solution of 5 mol nitric acid and 2 mol hydrofluoric acid, and soak for 10 min to chemically corrode and dissolve the Ag catalyst;

[0099] Step S 73 : The indium arsenide nanowires are taken out from the mixed solution and repeatedly cleaned with deionized water to remove the residues of the chemical corrosion solution;

[0100] Step S 74 : After 110 sccm of nitrogen was introduced into the InAs nanowires for 5 min, InAs nanowires without Ag catalyst were obtained.

[0101] Removing the catalyst Ag can avoid affecting the surface and interface properties of InAs nanowires, thereby maintaining the electrical, optical and chemical properties of InAs nanowires unchanged, improving the purity and stability of InAs nanowires, and thus optimizing their performance and applications.

[0102] Embodiment 3:

[0103] like Figure 3 and 5As shown, a method for preparing pure wurtzite crystal phase indium arsenide nanowires of the present invention comprises the following steps:

[0104] Step S1: Preparing the substrate layer 1 comprises the following steps:

[0105] Step S 11 : Prepare an indium arsenide layer with a thickness of 5 μm and a length and width of 60 μm as the substrate layer 1;

[0106] Step S 12 : The substrate layer 1 is chemically cleaned by a standard wet etching method using acetone, methanol, isopropanol and deionized water;

[0107] Step S 13 : Deoxidation treatment is performed on the substrate layer 1 using a hydrofluoric acid solution; the concentration of the hydrofluoric acid solution is: hydrofluoric acid: deionized water = 1:20;

[0108] Step S2: Use diamond nanoparticles to prepare graphene nanotubes 2 with a diameter of 30 μm and a length of 20 μm, and the length of the indium arsenide nanowires 3 is not greater than the inner diameter of the graphene nanotubes 2; place the prepared graphene nanotubes 2 longitudinally on the substrate layer 1; the size of the graphene nanotubes can be controlled by controlling the immersion time of the SiO2 substrate in the diamond suspension and the concentration of diamond nanoparticles in the diamond suspension to control the number and distribution of diamond nanoparticles adsorbed on the surface of the SiO2 substrate; then, the size of the graphene nanotubes is controlled by adjusting parameters such as the heating temperature, the flow rate of methane and hydrogen, and the reaction time; generally speaking, increasing the heating temperature and the methane flow rate can promote the growth rate and diameter of the graphene nanotubes, while also reducing their length. The specific preparation steps of the graphene nanotubes 2 are as follows:

[0109] Step S 21 : Disperse 0.03 g of 8 nm diamond nanoparticles in 200 ml of anhydrous ethanol to prepare a diamond suspension;

[0110] Step S 22 : Place a 50 nm thick SiO2 substrate in a diamond suspension and soak for 20 min;

[0111] Step S 23 : After the substrate plate is dried, the substrate plate is placed in a quartz tube of a horizontal resistance furnace and heated to 900° C. in an argon atmosphere to crack the diamond nanoparticles;

[0112] Step S 24: 1000 ml / min of methane and 100 ml / min of hydrogen are introduced to generate carbon atoms or carbon clusters; after reacting for 55 min, the methane and hydrogen are turned off, and the quartz tube of the electric furnace is cooled to room temperature under an argon atmosphere, and the carbon atoms or carbon clusters are aggregated on the SiO2 substrate to form graphene nanotubes;

[0113] Step S3: depositing a 1.0 nm thick Ag droplet as a catalyst on the substrate layer 1 below the graphene nanotube 2; Ag as a catalyst can inhibit the growth of indium arsenide molecules along the surface of the substrate layer 1, and the indium arsenide molecules only grow radially along the inner wall of the graphene nanotube, so that the obtained indium arsenide nanowire 3 has better quality;

[0114] Step S4: quickly transferring the graphene nanotubes and the substrate layer into the loading chamber of the MBE reactor, opening the reactor, and starting catalytic preparation of the indium arsenide nanowires 3;

[0115] Step S5: InAs molecules grow radially along the inner wall of the graphene nanotube 2, and the growth time of the InAs molecules is controlled to be 15 min, so that the InAs nanowire 3 of pure wurtzite crystal phase can be obtained, and then the MBE reactor is closed;

[0116] Step S6: heat-treating the treated graphene nanotubes to obtain graphene nanotubes opened along the longitudinal axis, and separating to obtain pure wurtzite crystal phase indium arsenide nanowires; the specific steps of radially opening the graphene nanotubes are as follows:

[0117] Step S 61 : Put the graphene nanotubes into an induction furnace and perform heat treatment at a temperature of 700 °C;

[0118] Step S 62 : After the heat treatment was continued for 60 min, 100 sccm of nitrogen was introduced into the induction furnace to rapidly cool the graphene nanotubes;

[0119] Step S 63 : Using a transmission electron microscope to observe whether the graphene nanotubes after heat treatment are successfully opened, if not successfully opened, repeating the heat treatment to obtain graphene nanotubes opened along the axial direction;

[0120] Step S7: The specific steps of removing the catalyst silver are as follows:

[0121] Step S 71 : Clean the indium arsenide nanowires prepared in step S6 with 200 ml of anhydrous ethanol, and repeat the cleaning twice to remove impurities and contaminants remaining on the surface of the indium arsenide nanowires;

[0122] Step S 72: Transfer the indium arsenide nanowires to a beaker, add a mixed solution of 4 mol nitric acid and 1.5 mol hydrofluoric acid, and soak for 20 min to chemically corrode and dissolve the Ag catalyst;

[0123] Step S 73 : The indium arsenide nanowires are taken out from the mixed solution and repeatedly cleaned with deionized water to remove the residues of the chemical corrosion solution;

[0124] Step S 74 : After 100 sccm of nitrogen was introduced into the InAs nanowires for 7 min, InAs nanowires without Ag catalyst were obtained.

[0125] Removing the catalyst Ag can avoid affecting the surface and interface properties of InAs nanowires, thereby maintaining the electrical, optical and chemical properties of InAs nanowires unchanged, improving the purity and stability of InAs nanowires, and thus optimizing their performance and applications.

[0126] Embodiment 4:

[0127] like Figure 4 and Figure 6 As shown, a method for preparing a two-dimensional layered structure of indium arsenide in a pure wurtzite crystal phase of the present invention comprises the following steps:

[0128] Step S1: Preparing the substrate layer 1 comprises the following steps:

[0129] Step S 11 : Prepare an indium arsenide layer with a thickness of 5 μm and a length and width of 60 μm as the substrate layer 1;

[0130] Step S 12 : The substrate layer 1 is chemically cleaned by a standard wet etching method using acetone, methanol, isopropanol and deionized water;

[0131] Step S 13 : Deoxidation treatment is performed on the substrate layer 1 using a hydrofluoric acid solution; the concentration of the hydrofluoric acid solution is: hydrofluoric acid: deionized water = 1:20;

[0132] Step S2: Use diamond nanoparticles to prepare graphene nanotubes 2 with a diameter of 30 μm and a length of 20 μm, and the diameter of the indium arsenide two-dimensional layered structure 4 is not greater than the inner diameter of the graphene nanotubes 2; place the prepared graphene nanotubes 2 longitudinally on the substrate layer 1; the size of the graphene nanotubes can be controlled by controlling the immersion time of the SiO2 substrate in the diamond suspension and the concentration of diamond nanoparticles in the diamond suspension to control the number and distribution of diamond nanoparticles adsorbed on the surface of the SiO2 substrate; then, the size of the graphene nanotubes is controlled by adjusting parameters such as the heating temperature, the flow rate of methane and hydrogen, and the reaction time; generally speaking, increasing the heating temperature and the methane flow rate can promote the growth rate and diameter of the graphene nanotubes, while also reducing their length. The specific preparation steps of the graphene nanotubes 2 are as follows:

[0133] Step S 21 : Disperse 0.02 g of 8 nm diamond nanoparticles in 150 ml of anhydrous ethanol to prepare a diamond suspension;

[0134] Step S 22 : Place a 50 nm thick SiO2 substrate in a diamond suspension and soak for 30 min;

[0135] Step S 23 : After the substrate plate is dried, the substrate plate is placed in a quartz tube of a horizontal resistance furnace and heated to 800° C. in an argon atmosphere to crack the diamond nanoparticles;

[0136] Step S 24 : 900 ml / min of methane and 90 ml / min of hydrogen are introduced to generate carbon atoms or carbon clusters; after reacting for 70 minutes, the methane and hydrogen are turned off, and the quartz tube of the electric furnace is cooled to room temperature under an argon atmosphere, and the carbon atoms or carbon clusters are aggregated on the SiO2 substrate to form graphene nanotubes;

[0137] Step S3: depositing a 1.0 nm thick Ag droplet as a catalyst on the substrate layer 1 below the graphene nanotube 2; Ag as a catalyst can inhibit the growth of indium arsenide molecules along the surface of the substrate layer 1, and the indium arsenide molecules only grow radially along the inner wall of the graphene nanotube, so that the obtained indium arsenide nanowire 3 has better quality;

[0138] Step S4: quickly transferring the graphene nanotubes and the substrate layer into the loading chamber of the MBE reactor, opening the reactor, and starting catalytic preparation of the indium arsenide nanowires 3;

[0139] Step S5: InAs molecules grow radially along the inner wall of the graphene nanotube 2 to form InAs nanowires. The growth time of the InAs molecules is controlled to be 100 min. The InAs nanowires grow along the graphene nanotubes and then undergo a self-aggregation effect and are bonded by van der Waals bonds to form an InAs two-dimensional layered structure 4. Then, the MBE reactor is closed.

[0140] Step S6: heat-treating the treated graphene nanotubes to obtain graphene nanotubes opened along the longitudinal axis, and separating to obtain a two-dimensional layered structure of indium arsenide in a pure wurtzite crystal phase; the specific steps of radially opening the graphene nanotubes are as follows:

[0141] Step S 61 : Put the graphene nanotubes into an induction furnace and perform heat treatment at a temperature of 600 °C;

[0142] Step S 62 : After the heat treatment was continued for 70 min, 90 sccm of nitrogen was introduced into the induction furnace to rapidly cool the graphene nanotubes;

[0143] Step S 63 : Using a transmission electron microscope to observe whether the graphene nanotubes after heat treatment are successfully opened, if not successfully opened, repeating the heat treatment to obtain graphene nanotubes opened along the axial direction;

[0144] Step S7: The specific steps of removing the catalyst silver are as follows:

[0145] Step S 71 : Clean the indium arsenide two-dimensional layered structure obtained in step S6 with 200 ml of anhydrous ethanol, and repeat the cleaning twice to remove impurities and contaminants remaining on the surface of the indium arsenide two-dimensional layered structure;

[0146] Step S 72 : The indium arsenide two-dimensional layered structure was transferred to a beaker, and a mixed solution of 3 mol nitric acid and 1 mol hydrofluoric acid was added and immersed for 30 min, so that the Ag catalyst was chemically corroded and dissolved;

[0147] Step S 73 : The indium arsenide two-dimensional layered structure is taken out from the mixed solution and repeatedly cleaned with deionized water to remove the residue of the chemical etching solution;

[0148] Step S 74 : After 90 sccm of nitrogen was introduced into the InAs two-dimensional layered structure for 10 min, an InAs two-dimensional layered structure without Ag catalyst was obtained.

[0149] Removing the catalyst Ag can avoid affecting the surface and interface properties of the InAs two-dimensional layered structure, thereby maintaining the electrical, optical and chemical properties of the InAs two-dimensional layered structure unchanged, improving the purity and stability of the InAs two-dimensional layered structure, and thus optimizing its performance and application.

[0150] Embodiment 5:

[0151] like Figure 4 and Figure 6 As shown, a method for preparing a two-dimensional layered structure of indium arsenide in a pure wurtzite crystal phase of the present invention comprises the following steps:

[0152] Step S1: Preparing the substrate layer 1 comprises the following steps:

[0153] Step S 11 : Prepare an indium arsenide layer with a thickness of 5 μm and a length and width of 60 μm as the substrate layer 1;

[0154] Step S 12 : The substrate layer 1 is chemically cleaned by a standard wet etching method using acetone, methanol, isopropanol and deionized water;

[0155] Step S 13 : Deoxidation treatment is performed on the substrate layer 1 using a hydrofluoric acid solution; wherein the concentration of the hydrofluoric acid solution is: hydrofluoric acid: deionized water = 1:20;

[0156] Step S2: Use diamond nanoparticles to prepare graphene nanotubes 2 with a diameter of 30 μm and a length of 20 μm, and the diameter of the indium arsenide two-dimensional layered structure 4 is not greater than the inner diameter of the graphene nanotubes 2; place the prepared graphene nanotubes 2 longitudinally on the substrate layer 1; the size of the graphene nanotubes can be controlled by controlling the immersion time of the SiO2 substrate in the diamond suspension and the concentration of diamond nanoparticles in the diamond suspension to control the number and distribution of diamond nanoparticles adsorbed on the surface of the SiO2 substrate; then, the size of the graphene nanotubes is controlled by adjusting parameters such as the heating temperature, the flow rate of methane and hydrogen, and the reaction time; generally speaking, increasing the heating temperature and the methane flow rate can promote the growth rate and diameter of the graphene nanotubes, while also reducing their length. The specific preparation steps of the graphene nanotubes 2 are as follows:

[0157] Step S 21 : Disperse 0.04 g of 8 nm diamond nanoparticles in 250 ml of anhydrous ethanol to prepare a diamond suspension;

[0158] Step S 22 : Place a 50 nm thick SiO2 substrate in the diamond suspension and soak for 10 min;

[0159] Step S23 : After the substrate plate is dried, the substrate plate is placed in a quartz tube of a horizontal resistance furnace and heated to 1000° C. in an argon atmosphere to crack the diamond nanoparticles;

[0160] Step S 24 : 1100 ml / min of methane and 110 ml / min of hydrogen are introduced, and after reacting for 45 minutes, the methane and hydrogen are turned off to generate carbon atoms or carbon clusters; the quartz tube of the electric furnace is cooled to room temperature under an argon atmosphere, and the carbon atoms or carbon clusters are aggregated on the SiO2 substrate to form graphene nanotubes;

[0161] Step S3: depositing a 1.0 nm thick Ag droplet as a catalyst on the substrate layer 1 below the graphene nanotube 2; Ag as a catalyst can inhibit the growth of indium arsenide molecules along the surface of the substrate layer 1, and the indium arsenide molecules only grow radially along the inner wall of the graphene nanotube, so that the obtained indium arsenide nanowire 3 has better quality;

[0162] Step S4: quickly transferring the graphene nanotubes and the substrate layer into the loading chamber of the MBE reactor, opening the reactor, and starting catalytic preparation of the indium arsenide nanowires 3;

[0163] Step S5: InAs molecules grow radially along the inner wall of the graphene nanotube 2 to form InAs nanowires. The growth time of the InAs molecules is controlled to be 140 min. The InAs nanowires grow along the graphene nanotubes and then undergo a self-aggregation effect and are bonded by van der Waals bonds to form an InAs two-dimensional layered structure 4. Then, the MBE reactor is closed.

[0164] Step S6: heat-treating the treated graphene nanotubes to obtain graphene nanotubes opened along the longitudinal axis, and separating to obtain a two-dimensional layered structure of indium arsenide in a pure wurtzite crystal phase; the specific steps of radially opening the graphene nanotubes are as follows:

[0165] Step S 61 : Put the graphene nanotubes into an induction furnace and perform heat treatment at a temperature of 800 °C;

[0166] Step S 62 : After the heat treatment was continued for 50 min, 110 sccm of nitrogen was introduced into the induction furnace to rapidly cool the graphene nanotubes;

[0167] Step S 63 : Using a transmission electron microscope to observe whether the graphene nanotubes after heat treatment are successfully opened, if not successfully opened, repeating the heat treatment to obtain graphene nanotubes opened along the axial direction;

[0168] Step S7: The specific steps of removing the catalyst silver are as follows:

[0169] Step S 71 : Clean the indium arsenide two-dimensional layered structure obtained in step S6 with 200 ml of anhydrous ethanol, and repeat the cleaning twice to remove impurities and contaminants remaining on the surface of the indium arsenide two-dimensional layered structure;

[0170] Step S 72 : The indium arsenide two-dimensional layered structure was transferred to a beaker, and a mixed solution of 5 mol nitric acid and 2 mol hydrofluoric acid was added and immersed for 10 min, so that the Ag catalyst was chemically corroded and dissolved;

[0171] Step S 73 : The indium arsenide two-dimensional layered structure is taken out from the mixed solution and repeatedly cleaned with deionized water to remove the residue of the chemical etching solution;

[0172] Step S 74 : After 110 sccm of nitrogen was introduced into the InAs two-dimensional layered structure for 5 min, an InAs two-dimensional layered structure without Ag catalyst was obtained.

[0173] Removing the catalyst Ag can avoid affecting the surface and interface properties of the InAs two-dimensional layered structure, thereby maintaining the electrical, optical and chemical properties of the InAs two-dimensional layered structure unchanged, improving the purity and stability of the InAs two-dimensional layered structure, and thus optimizing its performance and application.

[0174] Embodiment 6:

[0175] like Figure 4 and Figure 6 As shown, a method for preparing a two-dimensional layered structure of indium arsenide in a pure wurtzite crystal phase of the present invention comprises the following steps:

[0176] Step S1: Preparing the substrate layer 1 comprises the following steps:

[0177] Step S 11 : Prepare an indium arsenide layer with a thickness of 5 μm and a length and width of 60 μm as the substrate layer 1;

[0178] Step S 12 : The substrate layer 1 is chemically cleaned by a standard wet etching method using acetone, methanol, isopropanol and deionized water;

[0179] Step S 13 : Deoxidation treatment is performed on the substrate layer 1 using a hydrofluoric acid solution; wherein the concentration of the hydrofluoric acid solution is: hydrofluoric acid: deionized water = 1:20;

[0180] Step S2: Use diamond nanoparticles to prepare graphene nanotubes 2 with a diameter of 30 μm and a length of 20 μm, and the diameter of the indium arsenide two-dimensional layered structure 4 is not greater than the inner diameter of the graphene nanotubes 2; place the prepared graphene nanotubes 2 longitudinally on the substrate layer 1; the size of the graphene nanotubes can be controlled by controlling the immersion time of the SiO2 substrate in the diamond suspension and the concentration of diamond nanoparticles in the diamond suspension to control the number and distribution of diamond nanoparticles adsorbed on the surface of the SiO2 substrate; then, the size of the graphene nanotubes is controlled by adjusting parameters such as the heating temperature, the flow rate of methane and hydrogen, and the reaction time; generally speaking, increasing the heating temperature and the methane flow rate can promote the growth rate and diameter of the graphene nanotubes, while also reducing their length. The specific preparation steps of the graphene nanotubes 2 are as follows:

[0181] Step S 21 : Disperse 0.03 g of 8 nm diamond nanoparticles in 200 ml of anhydrous ethanol to prepare a diamond suspension;

[0182] Step S 22 : Place a 50 nm thick SiO2 substrate in a diamond suspension and soak for 20 min;

[0183] Step S 23 : After the substrate plate is dried, the substrate plate is placed in a quartz tube of a horizontal resistance furnace and heated to 900° C. in an argon atmosphere to crack the diamond nanoparticles;

[0184] Step S 24 : 1000 ml / min of methane and 100 ml / min of hydrogen are introduced to generate carbon atoms or carbon clusters; after reacting for 55 min, the methane and hydrogen are turned off, and the quartz tube of the electric furnace is cooled to room temperature under an argon atmosphere, and the carbon atoms or carbon clusters are aggregated on the SiO2 substrate to form graphene nanotubes;

[0185] Step S3: depositing a 1.0 nm thick Ag droplet as a catalyst on the substrate layer 1 below the graphene nanotube 2; Ag as a catalyst can inhibit the growth of indium arsenide molecules along the surface of the substrate layer 1, and the indium arsenide molecules only grow radially along the inner wall of the graphene nanotube, so that the obtained indium arsenide nanowire 3 has better quality;

[0186] Step S4: quickly transferring the graphene nanotubes and the substrate layer into the loading chamber of the MBE reactor, opening the reactor, and starting catalytic preparation of the indium arsenide nanowires 3;

[0187] Step S5: InAs molecules grow radially along the inner wall of the graphene nanotube 2 to form InAs nanowires. The growth time of the InAs molecules is controlled to be 120 min. The InAs nanowires grow along the graphene nanotubes and then undergo a self-aggregation effect and are bonded by van der Waals bonds to form an InAs two-dimensional layered structure 4. Then, the MBE reactor is closed.

[0188] Step S6: heat-treating the treated graphene nanotubes to obtain graphene nanotubes opened along the longitudinal axis, and separating to obtain a two-dimensional layered structure of indium arsenide in a pure wurtzite crystal phase; the specific steps of radially opening the graphene nanotubes are as follows:

[0189] Step S 61 : Put the graphene nanotubes into an induction furnace and perform heat treatment at a temperature of 700 °C;

[0190] Step S 62 : After the heat treatment was continued for 60 min, 100 sccm of nitrogen was introduced into the induction furnace to rapidly cool the graphene nanotubes;

[0191] Step S 63 : Using a transmission electron microscope to observe whether the graphene nanotubes after heat treatment are successfully opened, if not successfully opened, repeating the heat treatment to obtain graphene nanotubes opened along the axial direction;

[0192] Step S7: The specific steps of removing the catalyst silver are as follows:

[0193] Step S 71 : Clean the indium arsenide two-dimensional layered structure obtained in step S6 with 200 ml of anhydrous ethanol, and repeat the cleaning twice to remove impurities and contaminants remaining on the surface of the indium arsenide two-dimensional layered structure;

[0194] Step S 72 : The indium arsenide two-dimensional layered structure was transferred to a beaker, and a mixed solution of 4 mol nitric acid and 1.5 mol hydrofluoric acid was added and immersed for 20 min, so that the Ag catalyst was chemically corroded and dissolved;

[0195] Step S 73 : The indium arsenide two-dimensional layered structure is taken out from the mixed solution and repeatedly cleaned with deionized water to remove the residue of the chemical etching solution;

[0196] Step S 74 : After 100 sccm of nitrogen was introduced into the InAs two-dimensional layered structure for 7 min, an InAs two-dimensional layered structure without Ag catalyst was obtained.

[0197] Removing the catalyst Ag can avoid affecting the surface and interface properties of the InAs two-dimensional layered structure, thereby maintaining the electrical, optical and chemical properties of the InAs two-dimensional layered structure unchanged, improving the purity and stability of the InAs two-dimensional layered structure, and thus optimizing its performance and application.

[0198] Working principle of the present invention:

[0199] The pure wurtzite crystal phase indium arsenide nanowire structure prepared by the present invention is as follows Figure 3 As shown; InAs two-dimensional layered structure, such as Figure 4 As shown; the indium arsenide two-dimensional layered structure 4 is formed by the indium arsenide nanowires 3 being aggregated in the center of the graphene nanotubes 2 by the self-aggregation effect and the van der Waals force. The preparation process of the pure wurtzite crystal phase indium arsenide nanowires is as follows: Figure 5 As shown; the preparation process of indium arsenide two-dimensional layered structure, such as Figure 6 As shown; the growth time of indium arsenide molecules is controlled to be 10-20min, and indium arsenide nanowires of pure wurtzite crystal phase are prepared; the growth time of indium arsenide molecules is controlled to be 100-140min, so that the nanowires can grow into a two-dimensional layered structure. The preparation method of the present invention has a simple process, and there is no need to change the preparation steps. Indium arsenide nanowires or two-dimensional layered structures can be obtained by adjusting the production time, which can save production costs. Ag is used as a catalyst to inhibit the growth of indium arsenide nanowires on the substrate layer 1. The nanowires only grow on the inner wall of the graphene nanotube 2. The length of the resulting horizontally grown nanowires is controlled by the radius of the graphene nanotube. The crystal structure of the indium arsenide nanowires that can be generated is only a WZ structure, and the length can reach the micron level, thereby limiting the vertically grown indium arsenide nanowires to produce a ZB or WZ+ZB crystal structure when the length is too long, thereby making the device prepared by the indium arsenide nanowires of the present invention have better performance. The two-dimensional layered structure generated by the indium arsenide nanowires of the present invention can lead to a reduction in the effective carrier capture state, thereby improving terahertz radiation; in addition, based on the van der Waals force, the circumferential edge of the indium arsenide two-dimensional layered structure can be easily separated from the indium arsenide nanowires.

[0200] The above are preferred embodiments of the present invention. It should be pointed out that, for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as within the scope of protection of the present invention.

Claims

1. A method for preparing pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures, characterized in that: The following steps are involved: Step S1: preparing a substrate layer (1); Step S2: using diamond nanoparticles to prepare graphene nanotubes (2) of a desired size, and placing the prepared graphene nanotubes (2) longitudinally on the substrate layer (1) prepared in step S1; the specific preparation steps are as follows: Step S 21 : Disperse 0.02-0.04 g of 5-10 nm diamond nanoparticles in 150-250 ml of anhydrous ethanol to prepare a diamond suspension; Step S 22 : Place a SiO2 substrate with a thickness of 45-55 nm in a diamond suspension and soak for 10-30 min; Step S 23 : After the substrate plate is dried, the substrate plate is placed in a quartz tube of a horizontal resistance furnace and heated to 800-1000° C. in an argon atmosphere to crack the diamond nanoparticles; Step S 24 : 900-1100 ml / min of methane and 90-110 ml / min of hydrogen are introduced to generate carbon atoms or carbon clusters; after reacting for 45-70 min, the methane and hydrogen are turned off, and the quartz tube of the electric furnace is cooled to room temperature under an argon atmosphere, and the carbon atoms or carbon clusters are aggregated on the SiO2 substrate to form graphene nanotubes; Step S3: depositing Ag droplets with a thickness of 0.5-1.5 nm as a catalyst on the substrate layer (1) below the graphene nanotubes (2); Step S4: quickly transferring the graphene nanotubes and the substrate layer into the loading chamber of the MBE reactor, opening the reactor, and starting catalytic preparation of indium arsenide nanowires (3); Step S5: InAs molecules grow radially along the inner wall of the graphene nanotube (2), controlling the growth time of the InAs molecules to obtain InAs nanowires (3) or two-dimensional layered structures (4) in a pure wurtzite crystal phase, and then closing the MBE reactor; Step S6: heat-treating the graphene nanotubes processed in step S5 to obtain graphene nanotubes opened along the longitudinal axis, and separating to obtain pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures; the specific steps are as follows: Step S 61 : placing the graphene nanotubes treated in step S5 into an induction furnace and performing heat treatment at a temperature of 600-800° C.; Step S 62 : After the heat treatment is continued for 50-70 min, 90-110 sccm of nitrogen is introduced into the induction furnace to rapidly cool the graphene nanotubes; Step S 63 : Use a transmission electron microscope to observe whether the graphene nanotubes after heat treatment are successfully opened. If not, repeat step S 61 , S 62 , a graphene nanotube opened along the axial direction is obtained; Step S7: removing the catalyst silver from the indium arsenide nanowire or the two-dimensional layered structure, the specific steps are as follows: Step S 71 : Clean the indium arsenide nanowires or two-dimensional layered structures prepared in step S6 with 150-250 ml of anhydrous ethanol, and repeat the cleaning twice to remove impurities and contaminants remaining on the surface of the indium arsenide nanowires or two-dimensional layered structures; Step S 72 : Transfer the indium arsenide nanowires or two-dimensional layered structures into a beaker, add a mixed solution of 3-5 mol nitric acid and 1-2 mol hydrofluoric acid, and soak for 10-30 min to chemically corrode and dissolve the Ag catalyst; Step S 73 : Taking out the indium arsenide nanowires or two-dimensional layered structures from the mixed solution, and repeatedly washing them with deionized water to remove the residues of the chemical etching solution; Step S 74 : 90-110 sccm of nitrogen is introduced into the indium arsenide nanowire or two-dimensional layered structure for 5-10 minutes to obtain an indium arsenide nanowire or two-dimensional layered structure without Ag catalyst.

2. The method for preparing pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures according to claim 1, characterized in that: The specific preparation steps of step S1 are as follows: Step S 11 : Preparing an indium arsenide layer of a desired size as a substrate layer (1); Step S 12 : chemically cleaning the substrate layer (1) using a standard wet etching method using acetone, methanol, isopropanol and deionized water; Step S 13 : Using a hydrofluoric acid solution to deoxidize the substrate layer (1); wherein the concentration of the hydrofluoric acid solution is: hydrofluoric acid: deionized water = 1:

20.

3. The method for preparing pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures according to claim 1, characterized in that: The substrate layer (1) prepared in step S1 has a thickness of 4-6 μm and a length and width of 50-70 μm.

4. The method for preparing pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures according to claim 1, characterized in that: The graphene nanotube (2) prepared in step S2 has a diameter of 25-35 μm and a length of 15-25 μm.

5. The method for preparing pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures according to claim 1, characterized in that: In step S5, the growth time of the indium arsenide molecules is controlled to be 10-20 min, so that indium arsenide nanowires (3) in a pure wurtzite crystal phase can be obtained.

6. The method for preparing the pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures according to claim 1, characterized in that: In step S5, the growth time of the indium arsenide molecules is controlled to be 100-140 min, so that a two-dimensional layered structure (4) of indium arsenide in a pure wurtzite crystal phase can be obtained.

7. The method for preparing pure wurtzite crystal phase indium arsenide nanowires or two-dimensional layered structures according to any one of claims 1 to 6, characterized in that: The length of the indium arsenide nanowire (3) or the diameter of the two-dimensional layered structure (4) is no greater than the inner diameter of the graphene nanotube (2).

Citation Information

Patent Citations

  • Growing method of superfine indium arsenide nanowire with high crystalline quality

    CN103060905A

  • A nanowire device having graphene top and bottom electrodes and method of making such a device

    CN104145340A